PERAN PEMERINTAH DAERAH DAN MASYARAKAT DALAM PENGEMBANGAN DESA WISATA DI DESA SUKA SARI KECAMATAN KABAWETAN KABUPATEN KEPAHIANG - Henny Aprianty (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2019)
This study aims to determine and understand the role of local governments and communities in the development of tourism villages in Suka Sari village, Kabawetan district, Kepahiang district. This study uses a descriptive qualitative research approach, because the analysis of the data is in the form of written or oral words and considers the opinions of others that can be referred to as the resource persons. the results of the study concluded that the role of local government and the community was optimal. This can be seen from several indicators as follows: Indicators of aspects of the role of the government namely Providing Satisfaction to Tourists are quite satisfied in terms of the data of tourist visits which increases every year, Coordinating has been carried out by related parties with assistance in the development of tourist villages that are has been accepted by the village community. And indicators of aspects of the role of the community that is planned has been planned in the development of tourist villages have been implemented quite optimal